Perencanaan Sistem Pengolahan Air Limbah Domestik Pada Daerah Aliran Sungai Cibabat, Kota Cimahi - Mochammad Azhar Rais Alfaroby; Eka Wardhani (Jurnal Serambi Engineering, 2021)
The increase in population causes the need for clean water and community activities to increase and has an impact on increasing the amount of waste water produced. The amount of waste water that is generated depends on the large number of the population on the need for clean water used in every existing human activity. Domestic waste management in the Cibabat watershed area, Cimahi City is still minimal, in an effort to improve the quality of the Cibabat river and support the acceleration of pollution control in the Citarum watershed which is part of the Citarum Harum program in 2018, so a planning system for the distribution of domestic wastewater is needed Cibabat watershed, Cimahi City with the aim of producing domestic waste water that can be channeled and treated properly so that it does not pollute the aquatic environment. The method used in the planning of the domestic wastewater distribution system refers to the PUPR Regulation No. 04 of 2017 concerning guidelines for the implementation of the domestic wastewater management system. With the wastewater distribution system in the Cibabat watershed, it is hoped that it can improve the quality of water in the Cibabat River, Cimahi City in the planning period of the next 20 years. This study will determine the type of application of an effective domestic wastewater management system adapted to the existing conditions of the Cibabat watershed, Cimahi City.